Reproductive and productive characteristics in Bafra (Chios x Karayaka) ewes, growth, carcass performance and survivability of lambs - Koseman, Abdurrahman; Kul, Selim; Seker, Ibrahim; Kocyigit, Sezgin; Karaca, Mehmet (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
This study was carried out on Bafra (Chios x Karayaka) breed to determine the fertility characteristics of sheep, growth performance, survivability and carcass weights of lambs. For this purpose, the reproductive characteristics of 600 sheep aged 2-5 years and the survivability of 1,150 lambs born from these sheep were determined. In addition, the growth performance characteristics, slaughter, and carcass weights of 65 lambs born from 38 randomly selected ewes 3-4 years old were determined. In the study, the pregnancy rate was 90.00%, the birth rate was 87.16%, singleness 15.00%, twins 80.00%, and triplet 5.00%, lamb yield per ewe 1.90, number of lambs per birth 2.20 was calculated. Birth and weaning (90(th) d) weights as well as 61-90(th) d of live weight gains of male and female lambs were found as 4.26 and 3.57 kg, 24.15 and 21.32 kg, 265.75 and 231.72 g, respectively. The 120(th) d survivability, slaughter and carcass weights and carcass yields of lambs were determined as 97.74%, 47.10 kg, 21.61 kg and 45.92%, respectively. As a result, although the Bafra sheep is a breed that can be recommended to be raised in terms of the characteristics discussed, more scientific research is needed on it.
Características reproductivas y productivas en ovejas Bafra (Chios × Karayaka), crecimiento, rendimiento de la canal y supervivencia de los corderos
Keywords: Bafra sheep; growth performance; reproductive characteristics; lamb; survivability